Implementation of Computational Thinking - Based Active Learning in Presenting Environmental Friendly Simple Technology Products at MTsN 1 Tanah Datar - Azizah Rahmy (Literasi Nusantara, 2022)
Active learning thinking based on computational thinking is a learning approach that is needed by students in facing the 21st century. This research aims to find out how the process of applying active learning thinking based on computational thinking to environmentally friendly technology processes and products at MTsN (Islamic Junior High school) 1 Tanah Datar and its effect on activities and the learning outcomes of ix students at MTsN (Islamic Junior High school) 1 Tanah Datar . This research is the best practice from the author whose data are qualitative and quantitative. The result of this research is the application of active thinking learning based on computational thinking is very well applied to environmentally friendly technology processes and products. It can be seen from the increase of students' activity with an average of 4.24 (four point twenty-four) by good category and an increase of student learning outcomes with an average 95 (ninety-five) in the daily assessment of these basic competencies .